Value creation in art galleries: A service logic analysis. Issue 1 (February 2020) - Williams, Martin; Biggemann, Sergio; Tóth, Zsófia
Highlights: Travelling art exhibitions create customer, financial, sociocultural and professional value. Regional art galleries promote positive change around stereotypical views. Exhibitions bring (Aboriginal) social issues into wider public discourse. To implement service logic processes, galleries need research-based visitor knowledge. In-depth visitor research could help create more immersive (and competitive) experiences. Abstract: This study addresses how non-profit organisations like art galleries participate in co-creating value to visitors (customers), providers, and other stakeholders, and how these processes can be conceptualised within a service logic framework. We evaluate how an art gallery touring exhibition in regional Australia contributed to customer value, drawing on data collected in 2014–2016 from publications and websites, and interviews with staff of art galleries and arts organisations. Our findings illuminated four forms of value creation: financial, knowledge sharing, social and cultural, and professional value. Country art galleries have strong visitor orientation and employ co-creation processes focused on enhancing visitors' experience, aligned with government directions on Indigenous understanding and objectives of local Indigenous art communities. However, customer value exchange is not well understood. The lack of marketing research expertise and usable visitor data is a barrier to value creation. Chinese Abstract: 本研究探讨了像艺术画廊这样的非营利组织如何参与共同创造对游客 (顾客), 供应商和其他利益相关者的价值, 以及如何在一个服务逻辑框架中概念化这些过程. 我们利用 2014-2016 年从出版物和网站上收集的数据, 以及对画廊和艺术组织工作人员的采访, 评估了澳大利亚偏远地区的一个画廊巡展对客户价值的贡献. 我们发现并阐明了价值创造的四种形式: 财务, 知识共享, 社会文化和专业价值. 乡村艺术画廊有很强的游客导向, 并采用合作创作的过程以此来注重提高游客的体验, 符合政府对土著的理解和当地土著艺术社区的目标. 然而, 客户价值交换并没有被很好地理解. 缺乏市场调查专业知识和可用的访问者数据是价值创造的障碍.